Comparing impregnated of biomaterials with gentamicin as osteomyelitis treatment in New Zealand white rabbit – animal study - Zulkifly, Ahmad Hafiz; Mohd Jan, Nurul Hafiza; Aziz, Aziah; Ibrahim, Mohd Zulfadzli (2017)
Treatment of osteomyelitis is still a major problem in orthopedic field. New Zealand White rabbit (NZWR) is acceptable experimental model described to develop effective local delivery of antibiotics osteomyelitis treatment as it can mimics the disease process in human. The objective of this study was to analyze the treatment given via impregnated biomaterials with gentamicin beads in rabbit models. Osteomyelitis was developed by inoculation of Staphylococcus aureus ATCC 25923 into the drilled rabbit’s distal femur. Thirty-two (32) NZWR was used during the research. The rabbits were divided into 2 groups; (hydroxyapatite (HA) and calcium sulphate (CaSO4)) with four subgroups assessments in (3, 6, 12 and 26) weeks. The responses of the treatments against infection were evaluated through gross presentations, radiograph, micro CT, microbiology and histology. The rabbits were sacrificed accordingly to evaluate the healing process of bone. Results showed osteomyelitis changes were noted in all rabbit after inoculation of bacteria at week 3 intervals. Intervention was done after 3 weeks of inoculation. Chronic osteomyelitis was confirmed via radiology and microbial assessments. SPSS Version 23 was used to evaluate the results. The microbiology analysis revealed there was no bacterium isolated at 26th week interval in both group. Histology interpretation, healing was noted at site with appearance of new bone formation at 6 to 26 weeks of intervals. The micro CT results showed that trabeculae numbers increased significantly (p<0.05) with the treatment. The results show bone healing at 26th week of interval. There was no significant difference between both treatments modalities in the area of radiology, histology and micro CT assessment (p<0.05). The impregnated antibiotics biomaterial have its function in the treatment of osteomyelitis. In conclusion, these result showed that impregnated biomaterials with gentamicin have roles in treatment of osteomyelitis as added to medical and surgical treatment.